Učur tori (2005)
Das ist ein Informationsportal. Auf dieser Kategorie dieses Informationsportals finden sich Informationen über den Tourismus und Touristenziele in Xinjiang, China und im Ausland. - This is an information portal. On this category of this information portal you will find information about tourism and tourist destinations in Xinjiang, China and abroad.